Crickets (Insecta, Orthoptera, Grylloidea) from Southern New Caledonia, with descriptions of new taxa - Anso, Jérémy; Jourdan, Hervé; Desutter-Grandcolas, Laure (Zootaxa, 2016)
Intensive sampling of cricket communities has been undertaken in southern New Caledonia in selected plots of vegetation, i.e. rain forest, preforest and maquis shrubland. This leads to the discovery of many new taxa, which are described in the present paper, together with closely related species from nearby areas. Descriptions are based on general morphology and characters of genitalia. Calling songs are described for all acoustic taxa but two, and observations about species habitats are given. In total, 35 species belonging to 13 genera are studied, including 21 new species and two new genera. The pattern of assemblages of cricket species in New Caledonia is discussed.